The prognostic effect of pretreatment 18F-FDG PET/CT metabolic parameters in locally advanced esophageal squamous cell carcinoma treated with definitive chemoradiotherapy - Sakin, Abdullah; Özçelik, Mahsun; Şahin, Süleyman; Aydemir, Ozan; Aldemir, Mehmet Naci; İliklerden, Ümit Haluk; Kotan, Mehmet Çetin (Elsevier Science Ltd, 2022)
Introduction: In this study, we aimed to examine the relation between pre-treatment 18F-FDG PET/CT metabolic parameters [(including the maximum standard uptake value (SUVmax), metabolic tumor volume (MTV), and tumor lesion glycolysis (TLG)] and treatment response and survival in locally-advanced Esophageal Squamous Cell Cancer (ESCC) treated with definitive chemoradiotherapy (dCRT). Methods: A total 76 patients with locally-advanced ESCC who received dCRT between June 2015 and December 2019 were included in this retrospective study. Patients were divided into two groups as complete response (CR) or non-complete response (Non-CR) according to response to treatment. AUC was obtained as 0.749 (p < 0.001) in the ROC curve drawn by MTV for the CR. The MTV value was <= 12 cm(3), with 72.1% sensitivity and 73.0% specificity. Results: Of the 76 patients, 38 (50%) were male and 38 (50%) were female. The median age was 62 (39-84) years. The treatment response in 35 (46%) patients was CR. MTV value was > 12cm3 in 41(54%) patients. Median follow-up time was 14.5 months. In patients with MTV > 12cm3, median progression-free survival(mPFS) and median overall survival(mOS) were 9 months and 11 months, respectively, whereas mPFS and OS could not be reached in those with MTV & LE;12 cm3 (p < 0.001 and p < 0.001, respectively). In patients with non-CR, mPFS and mOS were 8 months and 9 months, respectively, whereas mPFS and OS could not be reached in patients with CR (p < 0.001 and p < 0.001, respectively). In multivariate analysis, age (odds ratio [OR], 1.07), ECOG PS (OR, 11.1), and MTV (OR, 4.73) were found to be the factors affecting treatment response. Conclusion: In our study, treatment response and MTV were found to be the factors associated with survival in patients treated with dCRT, showing the pre-treatment MTV value as a predictor of treatment response.
The prognostic effect of pretreatment 18F-FDG PET/CT metabolic parameters in locally advanced Esophageal Squamous Cell Carcinoma treated with definitive chemoradiotherapy: 18F-FDG PET/CT Metabolic Parameters in Esophageal Cancer
Keywords: Metabolic Tumor Volume; Tumor Lesion Glycolysis; Esophageal Cancer; Chemoradiotherapy; Squamous Cell Carcinoma